Analisis Inflasi, Tingkat Suku Bunga, Dividend Payout Ratio, dan Current Ratio terhadap Risiko Sistematis - Della Ferranti; Irni Yunita (Faculty of Economics and Business, University of Pasundan, 2015)
Investing is an activity that sacrifice the resources at this time in hopes of gaining greater profits in the future.. Before making an investment decision, an investor will consider many factors, one of which is about risk. There are two types of risk, systematic risk and unsystematic risk. Systematic risk is reflected in the value of beta coefficient. Beta indicates the volatility of stock return to market return. The purpose of this study was to determine the influence of inflation, interest rate, dividend payout ratio, and current ratio on systematic risk in State-owned Enterprises. This research was classified as descriptive verificative research. This study used data panel analysis with methods Common Effect Methods. These results indicate that inflation, interest rate, dividend payout ratio and current ratio does not have significant influence on systematic risk in State-owned Enterprises listed in Indonesia Stock Exchange period 2011-2013 either simultaneously or partially.